PERGUMULAN KULTUR DAN STRUKTUR DALAM MANAJEMEN ZAKAT DI POHUWATO GORONTALO - Ahmad Faisal (Al-Bayyinah, 2019)
AbstractThis article analyses the management of zakat by local governments. This study is focused on Pohuwato Regency in Gorontalo Province. As a relatively new religious idea, the idea of strengthening zakat management through the Regulations of the Regent is responded variedly by Muslim communities in this area. In general, they show responsive views. They are still categorized into two trends, namely, cultural and structural. This categorization is especially prominent when debating government involvement, community trust, socialization facts, and relevant distribution patterns. Even so, the tendency and categorization seemed to be significantly influenced by people's perceptions and knowledge of the whole discourse that accompanied the idea. Muslim communities generally agree with the Regents' Regulations on zakat, even though they do not know of its existence. Community turmoil only lies in the management of zakat. Keywords: Culture, Structure, Zakat Management.AbstrakArtikel ini menganalisa manajemen zakat oleh pemerintah daerah. Studi ini difokuskan di Kabupaten Pohuwato, Provinsi Gorontalo. Sebagai gagasan keagamaan yang relative baru, gagasan penguatan manajemen zakat melalui Peraturan Bupati ditanggapi secara variatif oleh masyarakat Muslim di daerah ini. Secara umum, mereka menunjukkan pandangan yang responsive, tetap saja terkategorisasi dalam dua kecendrungan, yakni kultural dan structural. Kategorisasi tersebut terutama menonjol ketika memperdebatkan keterlibatan pemerintah, kepercayaan masyarakat, fakta sosialisasi, dan pola distribusi yang relevan. Pun demikian, kecendrungan dan kategorisasi itu tampak sangat dipengaruhi oleh persepsi dan pengetahuan masyarakat terhadap keseluruhan wacana yang menyertai gagasan tersebut. Masyarakat muslim umumnya sepakat dengan Peraturan Bupati tentang zakat, meskipun mereka tidak mengetahui keberadaannya. Kegalauan masyarakat hanya terletak pada sistem pengelolaan zakat. Kata Kunci: Kultur, Struktur, Manajemen Zakat.